RANCANGAN SISTEM INFORMASI PENDUKUNG KEPUTUSAN PENETAPAN BONUS KARYAWAN MENGGUNAKAN METODE TOPSIS - Yogasetya Suhanda; Prasetyo Adi Nugroho; Alvia Alvia (Institut Teknologi dan Bisnis (ITB) Swadharma, 2022)
Information is important in carrying out an activity. Information technology is an important tool in supporting the performance of companies, both public and private, on a small, medium, or large scale. Information is expected to facilitate the work and achieve organizational goals. Information is an element that links management functions consisting of planning, operation, and control. Without information, a company will have difficulty in carrying out its operational activities. Therefore, to support the implementation of product and regular company information, a computerized system is needed. Employees can determine the progress of a company based on the performance of its employees. Generally, companies provide compensation in the form of bonuses to maintain a balance in the work ability of an employee to become more enthusiastic and responsible. In an effort to obtain complete and accurate data and information, the research method used to collect data and facts related to the problem discussed, field study research was carried out as a data collection technique. Based on the results of the analysis of hardware and software requirements, the proposed system design is declared technologically feasible and can be used. The system is designed using a web-based operational system, so that the resulting information can be accessed anytime and anywhere